2008
DOI: 10.1007/s10562-008-9644-9
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Suitability of a Pt-Based Catalyst for the Upgrading of a Biomass Gasification Syngas Stream via the WGS Reaction

Abstract: In this article, the catalytic activity of a Ptbased water gas shift (WGS) catalyst is presented. The experimental study has been conducted under realistic conditions typical of pressurised oxygen gasification. The effect of temperature, space velocity, steam to carbon monoxide ratio, and gas composition on the performance of the catalyst is investigated. Despite the high CO content in the feed gas, ranging from 32% to 60% v/v, dry basis, the catalyst has shown very good performance at intermediate temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…In addition, the improvement of hydrogen production was reported by adding Fe/CaO catalyst to a continuous-feed fluidized bed reactor [16]. Supported noble metal catalysts such as Rh, Ru and Pt have been reported to effectively increase syngas yield [18][19][20][21]. However, the high cost of these noble metals limits the wide applications of biomass gasification in industrial practice.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the improvement of hydrogen production was reported by adding Fe/CaO catalyst to a continuous-feed fluidized bed reactor [16]. Supported noble metal catalysts such as Rh, Ru and Pt have been reported to effectively increase syngas yield [18][19][20][21]. However, the high cost of these noble metals limits the wide applications of biomass gasification in industrial practice.…”
Section: Introductionmentioning
confidence: 99%
“…There are a variety of potential catalysts including bulk CaO with the attempts of numerous modifications that have been studied for biomass gasification process [7][8][9][10][11]. CaO is one promising catalyst material due to its lower cost and abundance.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, the WGS after a gasifier is carried out by a high-temperature (350 -400 °C), Fe-Cr-catalyst-based stage, followed by a low-temperature (220 -300 °C), Cu-Zn-catalyst-based shift with H2 being purified in a subsequent separation stage (Brunetti et al, 2012). However, the Fe-Cr-based catalysts pose potential environmental and safety issues due to the presence of Cr compounds, while the Cu-Zn-based catalysts tend to undergo sintering and are susceptible to poisoning (Maroño et al, 2008). The presence of H2 in syngas limits CO conversion thermodynamically (Eg.…”
Section: Syngas Upgradingmentioning
confidence: 99%
“…Chein et al (2014) showed that Pt/CeO2/Al2O3 catalysts exhibited good thermal stability in the temperature range of 750 -850 °C and bimetallic Pt-Ni/CeO2/Al2O3 catalysts led to higher CO conversion compared to monometallic catalysts (Pt/Al2O3 or Pt/CeO2/Al2O3). Maroño et al (2008) showed that the CO concentration at the reactor outlet was reduced to less than 3% using a Pt/CeO2/ZrO2 catalyst in the temperature range of 300 -400 °C, and CO conversion decreased as the space velocity increased or the H2O/CO ratio decreased.…”
Section: Syngas Upgradingmentioning
confidence: 99%